Adaptation “De Facto” ou Retour à l’Envoyer? L’Aide Déliée en Débat (Glocalism: Journal of Culture, Politics and Innovation, 2016)
The debate on aid effectiveness has been going on for some time especially in an environment of budgetary pressure on the various economies of CAD (Comité d’Aide au Développement) countries. This article questions the place of untied aid in development aid policies towards the African continent and gains in efficiency. If it is clear that the disbursement of Official Development Assistance has not reached its targets, it has adapted and evolved. The article analyzes the different implications of untied aid in terms of development and questions whether its emergence within the debate on the effectiveness would not be a smokescreen. For untied aid to be effective, some inherent contradictions have to be addressed. Untying aid in practice is subject to other constraints in recipient countries, and even untied aid finds itself in some way tied de facto.
Keywords: untied aid; trap; effectiveness; Africa; development